2018
DOI: 10.1208/s12249-018-0973-8
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ultra-Centrifugation and Bench-Top 19F NMR for Measuring Drug Phase Partitioning for the Ophthalmic Oil-in-Water Emulsion Products

Abstract: Generic drug products are expected to have the same active pharmaceutical ingredient (API) (Q1) with the same content (Q2) and microstructure arrangement (Q3) as the innovator product. In complex oil-in-water emulsion drugs, the hydrophobic API is mainly formulated in oil droplets stabilized by surfactant and micelles composed of extra surfactant molecules. The API phase partition in oil and water (mainly micelle) is a critical quality attribute (CQA) of emulsion product in demonstrating physicochemical equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…8 This is due to the unique challenge of the o/w soft matter nanocore, which is thermodynamically unstable 1,6 and subject to structural changes upon invasive separation. 9,12 Solution NMR spectroscopy was applied to study the solute transfer rate across the o/w interphase in an emulsion 13 and the drug release rate from the emulsion, which was in good agreement with in vivo results. 14 Both studies identified phasedependent chemical shift changes of solute molecules, 13,14 which supported NMR as an ideal noninvasive method for the drug phase distribution study in NE formulations.…”
Section: ■ Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…8 This is due to the unique challenge of the o/w soft matter nanocore, which is thermodynamically unstable 1,6 and subject to structural changes upon invasive separation. 9,12 Solution NMR spectroscopy was applied to study the solute transfer rate across the o/w interphase in an emulsion 13 and the drug release rate from the emulsion, which was in good agreement with in vivo results. 14 Both studies identified phasedependent chemical shift changes of solute molecules, 13,14 which supported NMR as an ideal noninvasive method for the drug phase distribution study in NE formulations.…”
Section: ■ Introductionsupporting
confidence: 56%
“…In the 19 F NMR spectrum of the DP sample DP-95%, that is, 95% (v/v) of DP mixed with 5% D 2 O, F28 peaks were observed in the range of −164.5−−167.0 ppm and F29 peaks in the range of −186.2−−187.4 ppm (Figure 1A), consistent with the previous 19 F chemical shift assignments. 12,15 In comparison with the F29 nucleus which had a chemical shift distribution of 1.2 ppm, the F28 nucleus was more sensitive to the chemical environment and had a broader chemical shift distribution of 2.5 ppm. Therefore, the peak of F28 was used as the reporter for the DFPN phase distribution throughout the study.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complex drug products can have molecular, compositional, or drug distribution heterogeneity, pertaining to differences in higher order structure, particle size distribution (PSD), 1,2 chemical composition, 3,4 or multiphase dosage forms. 5 These quality attributes can affect drug bioavailability, efficacy, safety, immunogenicity, and PK/PD properties, and present challenges for drug manufacturers and regulatory agencies to define robust and sensitive methods for measuring these critical quality attributes.…”
Section: Introductionmentioning
confidence: 99%